1996
DOI: 10.1073/pnas.93.20.10620
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution mapping of nucleoprotein complexes by site-specific protein-DNA photocrosslinking: organization of the human TBP-TFIIA-TFIIB-DNA quaternary complex.

Abstract: We have used a novel site-specific protein-DNA photocrosslinking procedure to define the positions of polypeptide chains relative to promoter DNA in binary, ternary, and quaternary complexes containing human TATAbinding protein, human or yeast transcription factor IIA (TFIIA), human transcription factor IIB (TFIIB), and promoter DNA. The results indicate that TFIIA and TFIIB make more extensive interactions with promoter DNA than previously anticipated. TATA-binding protein, TFHA, and TFIIB surround promoter D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
93
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(105 citation statements)
references
References 41 publications
10
93
0
Order By: Relevance
“…TBP and IIB exhibit patterns of crosslinking in the TBP-IIB-IIF-RNAPII-promoter complex similar to those previously reported for the TBP-DNA and TBP-IIB-DNA complexes (21) and in agreement with the crystallographic structures of the TBP-DNA and TBP-IIB-DNA complexes (16)(17)(18) (Fig. 1D).…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…TBP and IIB exhibit patterns of crosslinking in the TBP-IIB-IIF-RNAPII-promoter complex similar to those previously reported for the TBP-DNA and TBP-IIB-DNA complexes (21) and in agreement with the crystallographic structures of the TBP-DNA and TBP-IIB-DNA complexes (16)(17)(18) (Fig. 1D).…”
Section: Resultssupporting
confidence: 89%
“…To define positions of polypeptides relative to promoter DNA within the human TBP-IIB-IIF-RNAPII-promoter complex, we have performed site-specific protein-DNA photocrosslinking (ref. 21; Fig. 1).…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…3 Studies of TFIIA/TBP/TATA ternary complexes show that TFIIA contacts TBP as well as the DNA upstream and within the TATA box. [31][32][33][34][35][36] With the goal of obtaining a better understanding of the roles that TBP and TFIIA play in transcriptional regulation, we used FRET assays to accurately measure changes in the distance between the ends of the DNA upon binding TBP and TBP/TFIIA. We found that TFIIA enhances the stability of the bent state of TBP/TATA complexes, makes the complexes less sensitive to salt concentration, and causes the conformation of non-consensus TATA DNA bound by TBP to be the same as that of a consensus TATA box.…”
Section: Introductionmentioning
confidence: 99%